UV-activated adsorbents as novel materials for enhanced removal of malodorous gases. (March 2021) - Kim, Suho; Gupta, Nishesh Kumar; Bae, Jiyeol; Kim, Kwang Soo
Abstract: The performance of UV-activated Fe2 O3 -containing ZSM-5 (UFZ5) and silica (UFS) as adsorbents for the removal of low concentration of volatile organic sulfur compounds (VOSCs) was investigated in ambient conditions. A ∼99.9% and ∼89.2% removal of 10 ppm DMDS was observed for UFZ5 and UFS, respectively, due to a higher proportion of iron in UFZ5. The N2 adsorption isotherm confirmed an unpredictable increase in the surface area and pore volume of adsorbents after the fifth adsorption-oxidation cycle, which made adsorbents highly reusable for multiple cycles. The spectroscopic analysis predicted an increase in the hydroxyl density along with the resistance of catalytic sites against sulfur deactivation, which favored the adsorption-oxidation process. The adsorption capacity of UFZ5 remained in the range of 0.12–0.22, 0.26–0.48, 0.40–0.75 mg g −1 for methyl mercaptan (MM), dimethyl sulfide (DMS), and dimethyl disulfide (DMDS), respectively which were significantly higher than those calculated for UFS. The analysis confirmed SO2, CO, CH3 OH, H2 O, and elemental S as by-products. The UFZ5 was found competent and robust for the treatment of VOSCs-contaminated indoor air. Highlights: Efficient removal of VOSCs using UV-irradiated iron-containing ZSM-5 and silica. Increased surface area and pore volume after multiple cycles. GC-MS confirmed carbon monoxide, methanol, and water as by-products. Complete removal of 1 ppm of DMDS by UFZ5 within 5 min.